Burden of illness for patients with cholangiocarcinoma in the United States: a retrospective claims analysis - Chamberlain, Christina X. (J Gastrointest Oncol, 2021)
BACKGROUND: Advanced cholangiocarcinoma (CCA) is associated with considerable morbidity and mortality. Novel second-line treatments for advanced CCA underscore the need to understand treatment patterns and economic burden of illness in clinical practice. METHODS: This retrospective, claims-based study using Optum’s de-identified Clinformatics(®) Data Mart Database [2007–2019] selected patients with CCA who experienced failure of a line of therapy containing either gemcitabine or fluorouracil. The index date was defined based on evidence of treatment failure: date of last administration of the gemcitabine- or fluorouracil-based regimen plus 28 days, or initiation date of the next-line systemic therapy. Treatment patterns, healthcare resource use (HRU), costs, and survival were assessed during the follow-up period (index until death or end of eligibility). RESULTS: A total of 1,298 patients met inclusion criteria and had a mean age of 69.1 years. There were 958 patients (73.8%) with intrahepatic and 275 patients (21.2%) with extrahepatic CCA. Average follow-up was 7.5 months. Almost 40% of patients did not receive another line of therapy after the index date. Among the 784 patients who received another line of therapy, 40.3% used fluorouracil-based therapy, 30.7% used gemcitabine-based therapy, and 29.3% used capecitabine-based therapy. Total mean per patient per month CCA-related healthcare costs were $7,743, with medical services ($6,685) a larger driver of monthly costs relative to treatment costs ($1,058). Median overall survival (OS) was 5.3 months among all patients. CONCLUSIONS: Many patients with advanced CCA do not initiate additional therapy after failure of gemcitabine or fluorouracil treatment, and there is considerable variation in treatments among those who do. This study highlights the high costs and unmet need for a standard of care in this patient population.